ANALISIS PERBEDAAN TINGKAT LITERASI KEUANGAN PELAKU UKM - Lailan Safina Hasibuan; Susi Handayani; Lila Bismala (Universitas Lancang Kuning, 2022)
Financial management is one of the main problems in SMEs because if financial management does not go well, it will hamper performance and gain access to financing. Financial literacy becomes very important in financing decisions and their subsequent performance. Financial literacy enables entrepreneurs to manage risk through strategies, such as maintaining financial reserves, diversifying their investment portfolios and purchasing insurance. The purpose of this study was to determine the level of financial literacy of SME actors and to compare financial literacy between male and female SME actors. Data collection was carried out using a questionnaire to SME actors, with a sample of 384 SME actors in the culinary field. The results showed that the financial knowledge, financial attitudes and financial behavior of SME actors were good, meaning that they were able to carry out financial management well. Meanwhile, there are differences in financial knowledge and financial behavior between male and female SME actors, but the financial attitudes between male and female SME actors do not show any difference.